Ứng dụng các công cụ trí tuệ nhân tạo trong dạy học chủ đề “Con người và sức khỏe” (môn Tự nhiên và Xã hội lớp 3) - Phạm Thị Yến, Phạm Thị Yến; Bùi Nguyễn Phương Thùy, Bùi Nguyễn Phương Thùy; Lâm Tâm Như, Lâm Tâm Như (Tạp chí Giáo dục, 2026)
In the context of the rapid digital transformation within the education sector, the integration of Artificial Intelligence (AI) into instructional design has become an inevitable trend aimed at enhancing educational quality and innovating teaching methodologies. This study investigates the pedagogical potential of AI-based tools, including ChatGPT, Vbee, TTSMaker, Leonardo AI, Adobe Express, Adobe Firefly, CapCut, and Canva, in assisting teachers in designing lessons for the “Human and Health” topic in the Grade 3 Natural and Social Sciences subject. The approach is aligned with the competencybased and value-oriented goals of Vietnam’s 2018 General Education Curriculum. Employing document analysis, teacher-student surveys, the study reveals that the integration of AI significantly enhances the visual and interactive aspects of lessons, increases students’ engagement, and supports teachers in saving preparation time while diversifying instructional activities. The findings affirm the feasibility and pedagogical effectiveness of applying Artificial Intelligence in lesson design at the primary education level, thereby contributing to the successful realization of educational innovation in the era of digital transformation.